MAGICAL REALISM IN THE MYTH OF PULUNG GANTUNG IN GUNUNGKIDUL - Yohanes Angie Kristiawan; Yolanda Nadiandiru Susilo (JOLALI: Journal of Language and Literature, 2023)
Myth is a folk prose story that tells a story set in the past, contains an interpretation of the universe and the existence of creatures in it, and is considered to have happened by the owner of the story or its adherents. Myths can refer to traditional stories. According to Lugli (2014), myth is a “traditional story that is thought of by a specific community to be of a fundamental importance…”. As time goes by, myths are still present alongside contemporary literary works called magical realism literary works. Pulung Gantung in Gunungkidul is one of the mythical stories in the Gunungkidul area which is a literary work of magical realism. This study uses Wendy B. Faris' magical realism theory which consists of five elements, namely the irreducible element, the phenomenal world, merging realism, unsettling doubts and disruption of time, space and identity to determine the characteristics of magical realism in the story of the myth of Pulung Gantung in Gunungkidul. Those five elements were found after the interview with the relatives of the victim. The descriptive qualitative method was used to determine this study.